2019
DOI: 10.1177/0021998318819178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanofiller on the ageing of rubber seal materials under gamma irradiation

Abstract: The effect of high gamma irradiation and nanosilica on the structure and mechanical properties of the acrylonitrile butadiene rubber seal materials was investigated in this study. Acrylonitrile butadiene rubber nanocomposites containing (25, 50 and 75 phr) unmodified and modified nanosilica were irradiated at different doses (0, 0.2, 0.4, 0.6, 0.8, 1 MGy). The dispersion of nanosilica-based filler in acrylonitrile butadiene rubber was investigated by scanning electron microscope. Fourier-transform infrared ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It was found that the unfilled sponge EPDM exhibited the highest foaming degree, while the EPDM/f‐MWCNT nanocomposites exhibited the lowest foaming degree. Silane acted as a bi‐functional coupling agent and formed covalent bonds at the nanofiller–matrix interface 35 . In the curing process, the EPDM elastomer was first grafted by silane to form interfacial bonds and then covalent bonds (where the C = C double bond of the sponge EPDM and VTES coupling agent were broken to form C–C single bonds).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the unfilled sponge EPDM exhibited the highest foaming degree, while the EPDM/f‐MWCNT nanocomposites exhibited the lowest foaming degree. Silane acted as a bi‐functional coupling agent and formed covalent bonds at the nanofiller–matrix interface 35 . In the curing process, the EPDM elastomer was first grafted by silane to form interfacial bonds and then covalent bonds (where the C = C double bond of the sponge EPDM and VTES coupling agent were broken to form C–C single bonds).…”
Section: Resultsmentioning
confidence: 99%
“…3, which includes mycotoxins that are not classified as carcinogenic to humans [ 42 ]. The toxicity of ZEN in vivo was studied by many research mostly reported the hazardous effect of Zearalenone on the reproductive systems either in male or female [ 42 ], also there was a specific concern about the lipid peroxidation of membranes which is included in the means by which ZEN exert its toxic action on human [413, another concern was the findings of [ 44 ] who demonstrated the ability of Zearalenone to disrupt liver functions and affect the liver thoroughly to the degree of suppression of cytochrome P450 in the liver results of our work gave clear data about the distribution of Zearalenone in different body organs which in turn could reveal the most susceptible organs that could suffer from Zearalenone/derivatives toxicity [ [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] ]. By examining the beneficial effect of L. plantarum on the organ exposure to Zearalenone/derivatives, results revealed that although the administration of L. plantarum did not significantly alter the accumulation of [ 125 I]-iodo-ZEN in different mice organs and there were observed similarity in the pattern of Zearalenone distribution through different organs yet there was marked reduction in the Zearalenone concentration in the ovary and that was observed from the 1st 5 min of administration, and since the ovaries are considered the most sensitive (target) organ of Zearalenone toxicity that could provide additional benefit for the use of LAB as it was reported to demonstrate anti-inflammatory, anti-genotoxic and improve ovarian fertility [ 45 ], the decline in the accumulation of [ 125 I]iodo ZEN in mice organs may be attributed to the lactic acid bacterial capability to bind and/or alter ZEN to other compound [ 9 ].…”
Section: Discussionmentioning
confidence: 97%
“…12 Dispersion of nanosilica can be improved by lowering its surface energy. 6 Various surface modification techniques like passivation by plasma, electron beam, or physical modification with surfactants are employed for this. The consumption of silanol groups during surface modification creates reactive sites that facilitate interfacial bonding.…”
mentioning
confidence: 99%
“…13 Reinforcement of elastomers with nanosilica have enhanced cure characteristics, mechanical properties, swelling coefficients, radiation shielding, and so on. 6,11 Ethylene Propylene Diene Monomer (EPDM) rubber reinforced with both micro and nano silica exhibited remarkable mechanical and heat resistance properties. 1 Seyed Mostaffa Hosseini and Mehdi Razzaghi-Kashanihave investigated the vulcanization kinetics of nanosilica reinforced SBR (Styrene-Butadiene-Rubber) and found that nanosilica supported the curing reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation